Predictors of Counterproductive Workplace Behaviors of Nurses - Johnny Yao.jr (ACHSM, 2021)
Disruptive actions in healthcare settings can cause errors, poor client satisfaction, employee turnover, and bigger hospital expenses. This research investigated the determinants of counterproductive work behavior (CWB) such as work-related proactive coping, autonomy, interpersonal conflict, organizational constraints of hospital nurses in a tertiary hospital in large metropolitan city in the Philippines. A descriptive correlational design was utilized in the study. Nurses from the different clinical areas of the hospital were chosen as respondents for this study. Proactive coping received the strongest weight in the model followed by autonomy and organizational constraints; interpersonal conflicts received the lowest of the four weights. Based on the results of the study, the researcher can conclude that work-related proactive coping, autonomy, interpersonal conflicts, and organizational constraints are determinants of counterproductive work behaviors of hospital nurses. Health care managers should formulate customized programs and strategies that can improve employee performance and coping to reduce counterproductive work behaviors. Lastly, further studies would be conducted on other variables that can predict and mediate with counterproductive work behaviors.